(untitled) (Journal of the College of Basic Education, 2023)
Summary of the research:We have come to know that the ruler in determining the linguistic meaning of speech is understanding the letters of the goal, and from those letters (to, until) it is through them that we understand the end of the goal, so we can define the legal ruling in which we find the concept of the goal as the fundamentalists put it.the introduction:Praise be to God, Lord of the worlds, and prayers and peace be upon the most honorable of all creation, beloved of the God of the worlds, Abi Al-Qasim Muhammad, and his good and pure family, and after:Understanding the purpose is controlled by understanding the speech, especially the definition of the legal ruling. So you will find in the books of fundamentals in the section on concepts the concept of purpose that the fundamentalists satiated with in search, and they differed in determining the beginning of washing hands in ablution; To multiply the understanding of the purpose and its end.The field of research was Nahj al-Balaghah of Imam Ali, peace be upon him. Hence the importance of this research.And I ask Him, Glory be to Him, to grant us success in what He loves and is pleased with, for the sake of Muhammad and his pure family.end characters (to, until)